THE GEOMORPHOLOGIC FEATURES OF INTRUSIVE MAGMATIC STRUCTURES FROM BÂRGĂU MOUNTAINS (EASTERN CARPATHIANS, ROMANIA) - Bâca, Ioan (REVISTA GEOGRÁFICA ACADÊMICA, 2016)
Igneous intrusive structures from Bârgău Mountains belong to the group of central Neogene volcanic chain of the Eastern Carpathians of Romania. The evolution of the relief developed on these structures are three main stages: the stage of injection of structures (Pannonian), the stage of uncovering of igneous intrusive bodies from Oligo-Miocene sedimentary cover (Pliocene), and the stage of subaerial modeling of magmatic bodies (Pliocene-current).In those circumstances, the geodiversity of intrusive magmatic structures from Bârgău Mountains is represented by several types of landforms such as: polycyclic landforms (erosional levels), structural landforms (the configuration of igneous intrusive structures), petrographic landforms (andesites, lithological contact), fluvial landforms (valleys, slopes, ridges), periglacial landforms (cryogenic and crionival landforms), biogenic and anthropogenic landforms. This study highlights certain features of the landforms modeled on igneous intrusive bodies with the aim of developing some strategy for tourism recovery by local and county authorities.